Evaluación de Políticas de Protección en el Sector Papicultor mediante Sistemas Dinámicos:Caso Villapinzón (Cundinamarca) - Farfán Pinzón, Milena; Peña Ardila, Geimar (Ingeniería, 2015)
The potato production system is an economic activity of great importance in cold areas of the Andina Region (South America). In Colombia it is the main agricultural activity of peasant farmers in cold weather regions, carried out with little technological infrastructure and limited level of agriculture business management, whose production is incurring in soaring costs and whose profitability is highly-dependent on fluctuating market prices. In this paper the dynamical systems approach is used to model the context of the production system. The impact of current government protection policies to potato grower sector compared to the proposed policies obtained from the dynamical systems analysis are evaluated, with a particular attention to the town of Villapinz´on, in the Cundinamarca county (the largest municipality in Colombia with potato crops). It is shown that the proposed policies contribute to improving the financial earnings of the peasant farmers. For this purpose a model of structured analysis to measure the impact of these policies on the performance indicators of the system is developed and described.